Neuroprotective effects of a biodegradable poly(lactic-co-glycolic acid)-ginsenoside Rg3 nanoformulation: a potential nanotherapy for Alzheimer's disease?. (7th February 2018) - Aalinkeel, Ravikumar; Kutscher, Hilliard L.; Singh, Ajay; Cwiklinski, Katherine; Khechen, Noor; Schwartz, Stanley A.; Prasad, Paras N.; Mahajan, Supriya D.
Abstract: It is well established that overproduction and accumulation of the β-amyloid (Aβ) peptide 1–42 (Aβ(1–42)) is a trigger of the pathological cascade in Alzheimer's disease (AD) that manifests as cognitive impairment. Ginsenoside Rg3 is an important constituent of ginseng, plays an essential role in memory and improved cognition, and is known to produce antioxidant effects via the reduction of free radicals. Therefore, ginsenoside Rg3 may be a promising candidate as a neuroprotective agent for the treatment of AD. A novel nanotherapeutic strategy that enhances delivery of ginsenosides to the brain by increasing its transport across the blood brain barrier (BBB) would facilitate neuroprotection and limit the accumulation of Aβ plaques and subsequent neurodegeneration. In this current study, we formulated and characterised biodegradable poly(lactic-co-glycolic acid) (PLGA) nanoparticles (NPs) that encapsulate ginsenoside Rg3 and Thioflavin T, an Aβ diagnostic; examine its neuroprotective effects; investigate key mechanisms that may underlie its neuroprotective effects; and evaluate its ability to cross the BBB using an in vitro BBB model. Our PLGA-Rg3 NPs offers an exciting new theranostic material capable of encapsulating natural nutraceuticals for the detection and treatment of AD. In addition, this nanotechnology strategy can be adapted to treat other neurological diseases, utilising many natural therapeutic agents which are limited by their solubility and/or poor pharmacokinetics.